2013
DOI: 10.1007/s13762-013-0248-6
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer risk associated with residential proximity to industrial installations: a spatial analysis

Abstract: Lung cancer is the most common cause of cancer-related death and thus a major public health problem. While lung cancer frequency might be partially attributable to smoking habit and occupational exposure, the role of industrial pollution also needs to be assessed. To ascertain the possible effect of residential proximity to industrial installations on lung cancer risk in Asturias, an industrial region in Spain, taking into account the type of industrial activity and carcinogenic substances released. We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…We have used several distances (2, 3, 4 and 5 km) that coincide with that used by other authors (Cambra et al, 2013;Huang and Batterman, 2000;LopezAbente et al, 2012;Lopez-Cima et al, 2013;Pascal et al, 2013;Yang et al, 2003) and could be justified because, in these types of studies, if some increase in risk were to be found, it would most likely be in areas neither too close nor too far from pollutant sources. Moreover, the choice of 5 km has provided satisfactory results in the statistical analyses in similar ecologic studies (Federico et al, 2010;Garcia-Perez et al, 2013).…”
Section: Pollutantmentioning
confidence: 99%
“…We have used several distances (2, 3, 4 and 5 km) that coincide with that used by other authors (Cambra et al, 2013;Huang and Batterman, 2000;LopezAbente et al, 2012;Lopez-Cima et al, 2013;Pascal et al, 2013;Yang et al, 2003) and could be justified because, in these types of studies, if some increase in risk were to be found, it would most likely be in areas neither too close nor too far from pollutant sources. Moreover, the choice of 5 km has provided satisfactory results in the statistical analyses in similar ecologic studies (Federico et al, 2010;Garcia-Perez et al, 2013).…”
Section: Pollutantmentioning
confidence: 99%
“…Thirdly, physical environmental factors could result in regional inequalities in lung cancer mortality. Individuals living close to industrial installations, especially around metal industries, cement plants and shipyards, generally experience increased lung cancer risks [ 20 ]. Residents of coal-mining areas were found to have increased levels of lung cancer mortality as well [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to industrial sources, the European Commission passed the Integrated Pollution Prevention and Control (IPPC) in 2002 and the European Pollutant Release and Transfer Register (E-PRTR) in 2007. IPPC and E-PRTR records constitute an inventory of geo-located industries with health and environmental impact in Europe, which is a valuable resource for monitoring industrial pollution and, by extension, renders it possible for the association between residential proximity to such pollutants installations and health impacts, such as cancer, to be studied (Lopez-Cima et al, 2011;Lopez-Cima et al, 2013).…”
mentioning
confidence: 99%